Pathological response following neoadjuvant immunotherapy and imaging characteristics in dMMR/MSI-H locally advanced colorectal cancer - Deng, Zijian; Luo, Yajun; Chen, Xiaoli; Pan, Tao; Rui, Yuanyi; Hu, Hai; Yan, Jin; Zhang, Ke; Luo, Cheng; Song, Bo (Frontiers in Immunology, 2024)
In recent years, there has been significant research interest in immunotherapy for colorectal cancer (CRC). Specifically, immunotherapy has emerged as the primary treatment for patients with mismatch repair gene defects (dMMR) or microsatellite highly unstable (MSI-H) who have colorectal cancer. Yet, there is currently no data to support the practicality and safety of neoadjuvant immunotherapy for colorectal cancer with dMMR or MSI-H. Therefore, a study was conducted to identify the postoperative pathology, safety profile, and imaging features of patients with dMMR or MSI-H CRC following neoadjuvant immunotherapy. The retrospective study was carried out on patients with locally advanced or metastatic CRC who received immunotherapy at Sichuan Cancer Hospital, with approval from the hospital's ethics committee. The study aimed to assess the short-term effectiveness of immunotherapy by focusing on pathological complete response (pCR) as the primary outcome, while also considering secondary endpoints such as objective response rate, disease-free survival, and safety profile. Twenty patients with dMMR/MSI-H CRC who underwent neoadjuvant immunotherapy as part of the treatment were enrolled between May 2019 and February 2024 at Sichuan Cancer Hospital. Out of these patients, eight patients received PD-1 blockade monotherapy as neoadjuvant treatment, while 12 were administered a combined therapy of anti-CTLA-4 and anti-PD-1. 12 patients received Nivolumab plus Ipilimumab regimen and 8 patients received PD-1 blockades (2 patients were Pembrolizumab, 2 patients were Sintilimab, 4 patients were Tislelizumab) monotherapy. Additionally, 19 patients underwent surgery after immunotherapy and of these, 15 (75.0%) achieved complete pathological response (pCR), 8 (66.7%) achieved the same on Nivolumab plus Ipilimumab immunotherapy while 7 (87.5%) achieved on PD-1 antibody monotherapy. The overall response rate (ORR) was 75%, with 45.0% of patients experiencing grade I/II immunotherapy-related adverse events. The most frequent adverse event observed was increased ALT i.e. 20%. Notably, no postoperative complications were observed. Based on the findings, neoadjuvant immunotherapy for colorectal cancer may be both safe and effective in clinical practice. Furthermore, the study suggested that dual immunotherapy could potentially increase the immunotherapy cycle and contribute to a superior pCR rate. However, the conclusion emphasized the need for further prospective clinical trials to validate these results.